2013
DOI: 10.7202/1018437ar
|View full text |Cite
|
Sign up to set email alerts
|

Dis-identification in Organizations and Its Role in the Workplace

Abstract: Considerable theory and research has revealed that organizational identification (OID) benefits individuals and groups and that OID facilitates the development of long-term commitment and support towards an organization. Prior studies have highlighted the importance of an identification mechanism in the workplace, i.e., how employees define their self-concepts vis-à-vis their connections with their organizations. In contrast to previous research, we explore the process b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…For N, we used participants’ responses to five items taken from Kreiner and Ashforth's () scale of organizational disidentification (α = .89; sample item: ‘This organization does shameful things’). As in prior research (e.g., Chang et al, ; Kreiner and Ashforth's, ), the scales were negatively and moderately correlated (r = –.34, p < .01).…”
Section: Studysupporting
confidence: 77%
“…For N, we used participants’ responses to five items taken from Kreiner and Ashforth's () scale of organizational disidentification (α = .89; sample item: ‘This organization does shameful things’). As in prior research (e.g., Chang et al, ; Kreiner and Ashforth's, ), the scales were negatively and moderately correlated (r = –.34, p < .01).…”
Section: Studysupporting
confidence: 77%
“…Previous studies found that ODI was positively associated with intra-role conflict, negative affect, and cynicism ( Kreiner, 2002 ), person-organization fit and abusive supervision ( Chang et al, 2013 ) while negatively with organizational reputation, psychological contract fulfillment, negative affect, and individualism ( Kreiner, 2002 ). Disidentification may take multiple forms, including cynicism, humor, skepticism, and irony ( Costas and Fleming, 2009 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perhaps also, organisations struggling to survive may be more prone to negative gossip and ECN. Similarly, although JRG and NJG are found to have different relationships with ECN, we cannot assert whether the findings are applicable to other outcome variables, such as organisational identification and citizenship behaviour, which are found to be crucial in influencing organisational performance (Chang et al, 2013). Finally, Abraham (2000) indicates that cynicism may be related to personality, so we recommend future studies to consider personality factors, so that the knowledge of ECN may continue to be advanced.…”
Section: Limitation and Future Directionsmentioning
confidence: 99%
“…For instance, when facing gossip such as false information, individuals may feel stressed and uncomfortable with their organisation (the location of the gossip) and, consequently, alienate themselves from the organisation. In addition, a recent study (Chang, Kuo, Su, & Taylor, 2013) has found that organisational dis-identification (a type of alienation) is correlated with workplace deviance. This finding offers a preliminary but crucial clue to supporting the gossip -cynicism relationship.…”
Section: New Construct Of Workplace Gossip and Its Role In Employee Bmentioning
confidence: 99%
See 1 more Smart Citation